Beyond 2000: An Assessment of Infrastructure Policies - Ramonette B. Serafica (Philippine Institute for Development Studies (PIDS), 1998)
Infrastructure is a critical policy area affecting investment, productivity and equity within the aggregate strategy for attaining sustainable growth and development. A study by World Bank indicates a need between 38 to 48 billion for the Philippines to meet the country's investment requirements for infrastructure. This paper presents an assessment of the current infrastructure policies to determine whether or not reforms undertaken have been appropriate and congruent to the country's goal of sustainable growth and development. Policy recommendations are also given.
Keywords: 330; infrastructure; competition policy